Contemporary cryptology the science of information integrity - Simmons, Gustavus J. (IEEE Press, 1992)
The field of cryptography has experienced an unprecedented development in the past decade and the contributors to this book have been in the forefront of these developments. In an information-intensive society, it is essential to devise means to accomplish, with information alone, every function that it has been possible to achieve in the past with documents, personal control, and legal protocols (secrecy, signatures, witnessing, dating, certification of receipt and/or origination). This volume focuses on all these needs, covering all aspects of the science of information integrity, with an emphasis on the cryptographic elements of the subject. In addition to being an introductory guide and survey of all the latest developments, this book provides the engineer and scientist with algorithms, protocols, and applications. Of interest to computer scientists, communications engineers, data management specialists, cryptographers, mathematicians, security specialists, network engineers.